CYTOTOXIC AND ANTIBACTERIAL SESQUITERPENES FROM INULA-GRAVEOLENS - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 1993)
A further study on the aerial parts of Inula graveolens afforded a new eudesmanolide, 11,13-dihydroivalin and four known sesquiterpene lactones, ivalin, inuviscolide, 8-epi-inuviscolide, 8-epi-xanthatin-1beta,5beta-epoxide, in addition to the previously isolated compounds. The structures were established by spectral methods and the compounds were evaluated for their cytotoxic and antibacterial activity.
Keywords: INULA-GRAVEOLENS; COMPOSITAE; SESQUITERPENES; EUDESMANOLIDE; SPECTROSCOPY; CYTOTOXICITY; ANTIBACTERIAL ACTIVITY; OCCURRING TERPENE DERIVATIVES; LACTONES; XANTHANOLIDES; CONSTITUENTS; DITTRICHIA; AGENTS